The Happy Survivor? Effects of Differential Mortality on Life Satisfaction in Older Age - Segerstrom, Suzanne C. (Psychol Aging, 2016)
Older adults report higher psychological well-being than younger adults. Those highest in well-being also have the lowest risk of mortality. If those with lower well-being die earlier, it could affect the appearance of developmental change in well-being. In adults aged 50 and older (N=4,458), we estimated effects of differential mortality on life satisfaction by imputing life satisfaction, adjusting for attrition due to death, or estimating life satisfaction using pattern-mixture modeling. There was an increase in life satisfaction with age; however, differential mortality affected the elevation of the curve. Observed life satisfaction, particularly above age 70, is affected by differential mortality.